The Theoretical Description for Paracetamol and Naproxen Electrochemical Determination, Assisted by Conducting Polymer Composite with Cobalt (III) Oxyhydroxide - Volodymyr V. Tkach, Marta V. Kushnir, Lyudmyla V. Romaniv, Olga V. Pishak, Sílvio C. de Oliveira, Lucinda Vaz dos Reis, Yana G. Ivanushko, Bohdana Yu. Banul, Tetiana V. Honchar, Jarem R. Garcia, Adriano O. da Silva, Petro I. Yagodynets (My University, 2024)
A novel electroanalytical process for nitrite and sulfite anodic electrochemical determination in wine, based on the 9-triphenylphosphazoacridine conducting polymer as an anode modifier, has been investigated. 9-triphenylphosphazoacridine monomer may be obtained from 9-chloroacridine via 9- azidoacridine by reacting it with triphenylphosphine in ether. As for the sulfite and nitrite electrooxidation to sulfate and nitrate correspondently is given in conducting polymer matrix by two doping types. The analysis of the model has confirmed the efficiency of poly(9- triphenylphosphazo)acridine as an electrode modifier for sulfite and nitrite determination in wine, although the oscillatory behavior is relatively probable.
Letters in Applied NanoBioScience
Keywords: nitrite; sulfite; electrochemical sensor, acridine derivative; conducting polymer; electrochemical oscillations; stable steady-state